THE PROTECTION OF CONSUMER RIGHTS FOR AVIATION SAFETY AND SECURITY IN INDONESIA AND MALAYSIA - Annalisa Yahanan; Febrian Febrian; Rohani Abdul Rahim (Sriwijaya Law Review, 2017)
Indonesia and Malaysia have a good potency for cooperation in aviation industry. It can be seen in the establishing two aviation companies namely PT. Indonesia Air Asia and Malindo which both are low-cost carrier. These aviation industries are categorized as low-cost carrier, however safety and security are absolute factors because these are rights for consumers. This article will describe further about safety and security standard; protecting the rights for consumers in connection with safety aviation in Indonesia and Malaysia from the Consumer Protection Law and the Aviation Law. As a result of the research shows that safety standard passenger for air transportation in airport covers information and safety facility in the shape of availability of the emergency safety tools (fires, accidents and natural disasters); information, area and health facility; and healthcare workers. Moreover, safety standards for passenger in an aircraft include information and safety facility in the shape of availability information and the emergency safety tools for passenger in an aircraft. The protection for consumer rights for safety flight in Indonesia as follows: aviation industry has obligation to fulfill minimum standard of safety and security; consumers must be safety from false information which raises concern; aircraft operation which endanger of the passenger; and consumer protection in operating the electronic device which endanger flight. On the other hand, the law of consumer rights in Malaysia relating to aviation are ruled under the Aviation Law as a result of the Warsaw Convention 1929. In conclusion, the verdict of consumer rights related to security aviation begins when the passenger enter to an aircraft, in the aircraft, and by the time they get off the plane.